2010
DOI: 10.2139/ssrn.1343783
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Market Liquidity

Abstract: In this paper I analyze how corporate governance affects the performance of financial markets. I model the interaction between a firm's manager and its shareholders, and highlight the role played by the dividend report in information revelation and information transmission. The model shows that corporate governance mechanisms affect the market liquidity of the firm's stock (high monitoring costs and low ownership concentration lead to high market liquidity). Moreover, the effect of governance provisions that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In terms of operational transparency, better corporate governance can protect shareholders' interests and limit the activities that are not in line with the shareholders' best interests. Dumitrescu (2010) showed that corporate governance mechanisms affect the market liquidity of the firm's stock, as high monitoring costs, low ownership concentration, effective disclosure regulation and effective shareholder protection, lead to higher market liquidity. Leuz et al (2003) mentioned that corporate governance enhances financial transparency by mitigating the incentives and ability of managers to disclosure misleading information.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…In terms of operational transparency, better corporate governance can protect shareholders' interests and limit the activities that are not in line with the shareholders' best interests. Dumitrescu (2010) showed that corporate governance mechanisms affect the market liquidity of the firm's stock, as high monitoring costs, low ownership concentration, effective disclosure regulation and effective shareholder protection, lead to higher market liquidity. Leuz et al (2003) mentioned that corporate governance enhances financial transparency by mitigating the incentives and ability of managers to disclosure misleading information.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Under such condition of poor protection, investors will not be interested to invest in that country. Furthermore, Dumitrescu (2010) highlights that governance would affect market liquidity by improving the effectiveness of shareholders' protection that leads to greater liquidity. Since rule of law emphasizes on improving the fair and foreseeable rule as well as achieving greater shareholders' protection, this study suggests that a greater rule of law will lead to greater market liquidity through an increase in the number of participants.…”
Section: Moderating Effect Of Rule Of Lawmentioning
confidence: 99%
“…Furthermore, there is significant difference between presented definitions based on the country that it has been investigated [19]. Corporate governance is limited to relationship between a company and its shareholders [20]. This pattern is mentioned in the template of agency theory, while this conception may overstep relationship between company and its shareholders and defined in a network of relationship [21].…”
Section: Theoretical Underpinningsmentioning
confidence: 99%
“…Chesbrough recognize business model as crated value, identifying proportionate section of the market, defining structure of value chain, defining income generating mechanisms and corporation position in value chain and codification of competitive advantage that can be considered basis of open innovation [20].…”
Section: Theoretical Underpinningsmentioning
confidence: 99%